2020
DOI: 10.1021/jasms.0c00070
|View full text |Cite
|
Sign up to set email alerts
|

Atheroma-Specific Lipids in ldlr–/– and apoe–/– Mice Using 2D and 3D Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging

Abstract: Atherosclerosis is the major contributor to cardiovascular diseases. It is a spatially and temporally complex inflammatory disease, in which intravascular accumulation of a plethora of lipids is considered to play a crucial role. To date, both the composition and local distribution of the involved lipids have not been thoroughly mapped yet. Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) enables analyzing and visualizing hundreds of lipid molecules within the plaque while pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Here we focused on lipids as they are one of the main drivers of atherosclerosis, due to their role as mediators of many mechanisms involved in plaque progression and stability, including inflammation, VSMC proliferation and immune cell activation [ 19 ]. MALDI MSI has been used to investigate the lipid profile of mouse [ 20 , 21 , 22 , 23 , 24 ] and rabbit [ 25 , 26 ] plaques. A more systematic approach has been pursued [ 27 ] to investigate the lipid fingerprint of carotid plaque regions, and it was recently expanded to report the lipid profiles of the necrotic core, fibrin, foam cells, erythrocytes and calcified regions in human advanced carotid atheromas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here we focused on lipids as they are one of the main drivers of atherosclerosis, due to their role as mediators of many mechanisms involved in plaque progression and stability, including inflammation, VSMC proliferation and immune cell activation [ 19 ]. MALDI MSI has been used to investigate the lipid profile of mouse [ 20 , 21 , 22 , 23 , 24 ] and rabbit [ 25 , 26 ] plaques. A more systematic approach has been pursued [ 27 ] to investigate the lipid fingerprint of carotid plaque regions, and it was recently expanded to report the lipid profiles of the necrotic core, fibrin, foam cells, erythrocytes and calcified regions in human advanced carotid atheromas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies analyse data from a few human samples, e.g., to illustrate the potential for imaging lipid biochemistry in human atherosclerosis [ 53 ]. Recently, a 2-dimensional (2D) and three-dimensional (3D) MALDI-MSI study identified plaque-specific lipids in ApoE −/− and LDLR −/− mice [ 6 ]. In our study, we used MALDI MSI as a label-free and non-targeted method [ 45 ] for the direct comparison of murine and human atherosclerotic plaques to determine lipid markers for the differentiation of ApoE −/− from wild-type mice and for human atherosclerotic tissue samples with differences in progression and medication which, to the best of our knowledge, has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…This means, instead of demonstrating a qualitative validation, the work by Khamehgir-Silz et al [ 7 ] measured the differential lipid composition in quantitative terms, setting a new reference standard for plaque MALDI MIS. Another novel aspect of this work is the improved spatial resolution compared to previous studies [ 3 6 ] as Khamehgir-Silz et al achieved 7 µm for mouse and 5–15 µm for human samples, allowing for cellular resolution on the tissue level. This is important because it provides a map of the specific lipid location intima vs. media vs. adventitia.…”
mentioning
confidence: 91%
“…The comparison of young vs. older apoE-deficient mice sheds light on lipidomic changes during the progression of atherosclerosis. While previous studies started analyzing human atherosclerotic lesion samples by MALDI MIS [3][4][5][6], this investigation directly compared the lipid landscapes between mouse and human lesions with a robust sample number. This means, instead of demonstrating a qualitative validation, the work by Khamehgir-Silz et al [7] measured the differential lipid composition in quantitative terms, setting a new reference standard for plaque MALDI MIS.…”
mentioning
confidence: 99%